Trophic transfer of radioisotopes in Mediterranean sponges through bacteria consumption. (February 2016) - Lacoue-Labarthe, Thomas; Warnau, Michel; Beaugeard, Laureen; Pascal, Pierre-Yves
Abstract: Numerous field studies highlighted the capacities of marine sponges to bioaccumulate trace elements and assessed their potential as biomonitors of the marine environment. Experimental works demonstrated that dissolved metals and radionuclides can be taken up directly by sponge tissues but, to the best of our knowledge, little is known on the contribution of the dietary pathway through the consumption of contaminated bacteria considered as one of the trophic source in sponge diet. Objectives of this work are to study trophic transfer of radiotracers 110m Ag, 241 Am, 109 Cd, 57 Co, 134 Cs, 54 Mn and 65 Zn from the marine bacteria Pseudomonas stutzeri to the Mediterranean sponges Aplysina cavernicola and Ircinia oros. P. stutzeri efficiently bioaccumulated trace elements in our culture experimental conditions with CF comprised between 10 5 and 10 7 after 48 h of growth in radiolabeled medium. When fed with these radiolabelled bacteria, A. cavernicola took up around 60% of radiotracers accumulated in trophic source except 134 Cs for which only 8% has been transferred from bacteria to sponge. Contrasting to this, I. oros retained only 7% of 110m Ag, 109 Cd and 65 Zn counted in bacteria, but retained 2-fold longer accumulated metals in its tissues. The sponge inter-specific differences of accumulation and depuration following a trophic exposure are discussed with respect to the structure and the clearance capacities of each species. Highlights: We study the transfer of radioisotopes in two sponge species fed with bacteria. We radiolabelled Pseudomonas stutzeri with seven metals and radionuclides. We examine the metal accumulation in bacteria and uptake and retention in sponge. Massive sponge assimilated less metal but retained 2-fold longer than erect species. Massive sponge could be pertinent candidate as biomonitor of chronic contamination.